WHO PERFORMS BETTER IN ESSAY WRITING, INTROVERTS OR EXTROVERTS? A CASE STUDY OF 3RD SEMESTER EFL STUDENTS - Novi Rahmania Aquariza; Nailul Authar (Jurnal Inovasi Penelitian, 2020)
This research will investigate whether there are any significant differences between Introvert and Extrovert students on their Essay Writing performance. The object of this research will be the 3rd semester of EFL students in a private university in Surabaya academic year 2019-2020. This study will use ex post facto design with quantitative approach. For the data collection, this research will use questionnaire and documentations as the instruments. The students are all will have Writing III as the subject on that semester, totally 22 students will be the sample. This research also discuss the factors related such as what are the things influence this two types of personality in writing an Essay